2007
DOI: 10.1038/ng1987
|View full text |Cite
|
Sign up to set email alerts
|

A module of negative feedback regulators defines growth factor signaling

Abstract: Signaling pathways invoke interplays between forward signaling and feedback to drive robust cellular response. In this study, we address the dynamics of growth factor signaling through profiling of protein phosphorylation and gene expression, demonstrating the presence of a kinetically defined cluster of delayed early genes that function to attenuate the early events of growth factor signaling. Using epidermal growth factor receptor signaling as the major model system and concentrating on regulation of transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
484
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(526 citation statements)
references
References 50 publications
39
484
2
1
Order By: Relevance
“…Another aspect strengthening the hypothesis that targeting ZFP36 could impinge on GBM biology, resides on published data suggesting that ZFP36 negatively regulates EGFr pathway, 14 which is particularly important during the development of the disease, and that among its targets there's also Stat5b, 27 whose activity participates in determining the proliferative activity and the invasion capability of GBM cells. 29 To verify the effect of ZFP36 expression on GBM cells, we performed ectopic expression experiments and, while doing so, we demonstrated that the kinases PIM1 and PIM3 and X-linked inhibitor of apoptosis protein (XIAP) are new ZFP36 targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect strengthening the hypothesis that targeting ZFP36 could impinge on GBM biology, resides on published data suggesting that ZFP36 negatively regulates EGFr pathway, 14 which is particularly important during the development of the disease, and that among its targets there's also Stat5b, 27 whose activity participates in determining the proliferative activity and the invasion capability of GBM cells. 29 To verify the effect of ZFP36 expression on GBM cells, we performed ectopic expression experiments and, while doing so, we demonstrated that the kinases PIM1 and PIM3 and X-linked inhibitor of apoptosis protein (XIAP) are new ZFP36 targets.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 At the biological level, TTP family members have been described as involved in cell differentiation and apoptosis, 12,13 in the regulation of the cell response to growth factors and in the development of cancer. In particular, it has been demonstrated that TTP proteins target and destabilize mRNAs encoding growth factors' signaling transducers, particularly downstream of EGF 14 and IGF-I receptors. 4 Moreover, it has been recently suggested that members of this family are also capable of acting by ARE-mediated decay-independent mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that are responsible for this kind of selectivity have not been elucidated, but they could rely on feedback effects that are hard-wired into oncogene-addicted tumours. In the case of the EGF receptor, transcriptional induction of the dual specificity phosphatases (DUSPs), which are negative regulators of MAPK activity, has been proposed as a crucial step in modulating receptor signalling outputs 147 . Interestingly, DUSPs exert a promiscuous phosphatase activity on multiple members of the MAPK family 148 .…”
Section: Met Signalling In Development and Diseasementioning
confidence: 99%
“…An incoherent FFL in EGFR-mediated transcriptional circuits was recently described (Amit et al 2007). EGFR induces expression of the Zink Finger Protein 36 (ZFP36), which binds to AU-rich elements, predominantly found in the 3 0 -untranslated regions (3 0 -UTR) of unstable mRNA molecules, and promotes their deadenylation and subsequent degradation (Chen et al 2001).…”
Section: Rtk Network Are Tightly Controlled By Feedback and Feedforwmentioning
confidence: 99%
“…EGFR induces expression of the Zink Finger Protein 36 (ZFP36), which binds to AU-rich elements, predominantly found in the 3 0 -untranslated regions (3 0 -UTR) of unstable mRNA molecules, and promotes their deadenylation and subsequent degradation (Chen et al 2001). A systematic analysis of EGF-induced genes revealed that many of these genes contain such 3 0 -UTRelements, thus suggesting a widespread role of ZFP36 in IEG and DEG regulation (Amit et al 2007). Although ZFP36 does not affect gene transcription directly, it regulates the availability of multiple mRNA molecules, thereby forming an incoherent FFL (Fig.…”
Section: Rtk Network Are Tightly Controlled By Feedback and Feedforwmentioning
confidence: 99%